Перспективы использования аккумуляторных батарей в военной гусеничной и колесной технике - Бондарь, А. И.; Дегтярь, С. М.; Павленко, С. А.; Смоляков, В. А. (НТУ "ХПИ", 2013)
У статті розглянуто свинцево-кислотні, гелеві та AGM-батареї як найбільш придатні типи АКБ для використання їх у якості стартерних у військовій гусеничній та колісній техніці, їх переваги та недоліки. Для перспективних розробок запропоновано використання гелевих АКБ або AGM АКБ.

In article are considered SLA, GEL and AGM-batteries to the most comprehensible types batteries for their use in quality starter in the military caterpillar and wheel technics, their merits and demerits. For perspective workings out use GEL batteries or AGM-batteries is recommended.
Measurement of the charge of the liquid by means of the ultrasonic flowmeter
Keywords: аккумуляторные батареи; военная гусеничная техника; военная техника; танки; боевая машина